Food safety training needs assessment for independent ethnic restaurants: review of health inspection data in Kansas - Kwon, Junehee; Roberts, Kevin R.; Shanklin, Carol W.; Liu, Pei; Yen, Wen S.F. (International Association for Food Protection, 2011)
Each year, commercial foodservice operations in the United States serve over 70 billion meals/snacks. The majority of foodborne disease outbreaks have been attributed to commercial foodservice establishments, and independent ethnic restaurants received poorer inspection scores than the non-ethnic or chain restaurants. These findings imply additional need for food safety training for ethnic restaurant employees. To identify specific food safety training needs, online health inspection reports of 500 randomly-selected independent restaurants in 14 Kansas counties were reviewed. Food code violations were recorded and categorized for further analysis. Numbers of critical and non-critical violations, inspections within 12 months, and violations within each category for ethnic and non-ethnic restaurants were compared, using independent t-tests. Ethnic restaurants had more critical (4.52 ± 2.97) and non-critical violations (2.84 ± 2.85) and more frequent inspections (2.29 ± 1.63) than non-ethnic restaurants (2.90 ± 2.83, 1.71±1.94, and 1.76 ± 1.11, respectively, P < 0.001). Significantly more (P < 0.05) violations were reported in ethnic restaurants for several categories: time and temperature control of PHFs, physical facility maintenance, protection from contamination, hand hygiene, proper use of utensils, demonstrated knowledge, and food temperature control for non-PHF. The data suggested that ethnic restaurant personnel need increased food safety training, especially for critical behaviors such as time and temperature control and hand washing.
Keywords: Food safety; Foodborne disease; Ethnic restaurants; Training; Inspection; Kansas